IRE1α regulates ROS and immune responses after UVB irradiation - Jeongin Son; Jacob T Bailey; Stephen Worrell; Adam B Glick (Bioscientifica, 2024)
Objective: UV irradiation of the skin induces photo damage and generates cytotoxic intracellular reactive oxygen species (ROS), activating the unfolded protein response (UPR) to adapt or reduce these UVB-mediated damages. This study was designed to understand the role of the UPR mediator IRE1α in the antioxidant response following UVB irradiation of mouse skin and keratinocytes. Methods: We used mice with an epidermal deletion of IRE1α and primary mouse keratinocytes to examine effects of UV on different parameters of the antioxidant response in the presence and absence of functional IRE1α. Results: In the absence of IRE1α, PERK activity and protein levels are significantly compromised following UVB irradiation. Additionally, the loss of IRE1α suppressed phosphorylation of the PERK target, nuclear factor erythroid- 2-related factor 2 (NRF2), and NRF2-dependent antioxidant gene expression after UVB irradiation. Interestingly, IRE1α-deficient keratinocytes exhibit elevated basal ROS levels, while a robust ROS induction upon UVB exposure is abolished. Because UVB-induced ROS plays an essential role in regulating skin inflammation, we analyzed recruited immune cell populations and the expression of pro-inflammatory cytokines, Il-6 and Tnfα, in mice with epidermally targeted deletion of Ire1α. Following UVB irradiation, there was significantly less recruitment of neutrophils and leukocytes and reduced expression of pro-inflammatory cytokine genes in the skin of mice lacking IRE1α. Furthermore, keratinocyte proliferation was also significantly reduced after chronic UVB exposure in the skin of these mice. Conclusion: Collectively, our findings indicate that IRE1α is essential for basal and UVB-induced oxidative stress response, UV-induced skin immune responses, and keratinocyte proliferation. Significance statement These findings shed new light on the protective function of IRE1α in the response to UV. IRE1α plays an important role in the regulation of ROS, PERK stability, and antioxidant gene expression in response to UVB in mouse keratinocytes and epidermis.